The Impact of Grammar Knowledge on Student Proficiency in Malaysian Elementary Schools - Purnomo, Ryan; Azizah, Siti Nur; Shofi, Ahmad Thoyyib; Rahmawan, Ghanal Arief; Ramadhan, Rizki; Fauzi, Muhammad; Septianto, Tri (Cetta: Jurnal Ilmu Pendidikan, 2025)
This study aims to explore the relationship between explicit grammar knowledge and English proficiency levels among students. The study involved nine Indonesian teaching students who were divided into three groups, namely seven new teachers who were teaching English for the first time in elementary schools and two teachers who regularly taught English for communication. Data were collected through interviews and grammar assignments to assess their explicit grammar knowledge as well as their level of language proficiency. The results of the study showed that there was a tendency to associate explicit grammar knowledge and English proficiency. However, explicit grammatical knowledge is not the main determinant of proficiency level. In contrast, proficiency is more influenced by a combination of factors, such as individual preferences and study habits. Students who engage in implicit learning activities, such as regular communication and exposure to language in context, show higher levels of fluency than students who rely on explicit grammar instruction. Nonetheless, explicit grammatical knowledge remains important, especially in academic contexts that demand accurate and formal use of language. An approach that consciously integrates explicit grammar instruction is recommended to support skill development, especially in academic writing. In this way, implicit learning can improve fluency, while explicit learning favors accuracy and formal structure. In conclusion, combining explicit and implicit grammar knowledge into a balanced approach can improve overall fluency and accuracy. Teachers are advised to incorporate explicit grammar instruction into a context-based curriculum that supports immersive learning to optimize student language development.